2021
DOI: 10.3390/cancers13194996
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Radiofrequency Guided Localisation in Breast Surgery: A Systematic Review

Abstract: Wire-guided localisation (WGL) has been the gold-standard for localising non-palpable breast lesions before excision. Due to its drawbacks, various wireless alternatives have been developed, including LOCalizer™, which is based on radio-frequency identification (RFID) technology. In this systematic review, we consulted EMBASE, Medline and PubMed databases using appropriate search terms regarding the use of RFID technology in the localisation of occult breast lesions. Retrospective and prospective studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…For WL, Davey et al reported a positive margin rate of 20.1% and a surgical re-excision rate of 17.3% in a meta-analysis involving 24 randomized controlled trials [21]. In a review by Tayeh et al, the surgical re-excision rate for RFID localization was 13.9% [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For WL, Davey et al reported a positive margin rate of 20.1% and a surgical re-excision rate of 17.3% in a meta-analysis involving 24 randomized controlled trials [21]. In a review by Tayeh et al, the surgical re-excision rate for RFID localization was 13.9% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two on-going prospective, controlled studies assessing RFID localization are currently underway, but their results are not yet available [10,11]. All these studies, most included in a recent meta-analysis, have concluded that RFID tags are a potential alternative to hook wire and should be considered for localizing non-palpable breast lesions [12].…”
mentioning
confidence: 99%
“…Magseed is similar to the RFID system but is not able to offer the exact distance from the marker in mm, because it is based only on acoustic and visive information about the signal strength [12]. Both the systems are promising, and many studies encouraged the adoption of RFID breast localization for NPBL, particularly [15][16][17]. Wazir et al [18] reported the experience of a double tag placement.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2021 by Tayeh et al involved 1,151 patients and 1,344 RFID tags. The review concluded that the LOCalizer™ system is a valid, safe, and effective alternative to WGL ( 99 ). A recent study by Parisi et al showed that combined LOCalizer™ and US localization technique had superior oncological outcomes as compared to LOCalizer™ alone ( 23 ).…”
Section: Localization Methods For Non-palpable Breast Lesionsmentioning
confidence: 99%
“…It utilizes an introducer needle that is wider than the introducer needles of Magseed ® and Savi Scout ® . Therefore, deployment within dense breast tissue could potentially be difficult ( 99 ). Furthermore, the RFID system has similar limitations as radar technology, such as dislocation of the marker during insertion, hematoma, and limited detection range ( 100 ).…”
Section: Localization Methods For Non-palpable Breast Lesionsmentioning
confidence: 99%